2021
DOI: 10.14569/ijacsa.2021.0120705
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Network Steganography Detection based on Deep Learning Techniques

Abstract: One of the techniques that current cyber-attack methods often use to steal and transmit data out is to hide secret data in packets. This is the network steganography technique. Because millions of packets are sent and received every hour in internet activity, so it is very difficult to detect the theft and transmission of system data out using this form. Recent approaches often seek ways to compute and extract abnormal behaviors of packets to detect a steganography protocol or technique. However, such methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The study's goal [18] was to develop a method of discovering network steganography through the use of deep learning technology. The advantage of this study conducted by the researcher was found several techniques to hide the network.…”
Section: Introductionmentioning
confidence: 99%
“…The study's goal [18] was to develop a method of discovering network steganography through the use of deep learning technology. The advantage of this study conducted by the researcher was found several techniques to hide the network.…”
Section: Introductionmentioning
confidence: 99%